P80 Symptoms, delay to presentation and survival in lung cancer. (15th November 2016) - Chan, WY; Clark, A; Dernedde, U; Roques, T; Burton, M; Kotecha, J; Wilson, A; Martin, C
Abstract : Introduction and objectives: We aimed to study quantitatively the lung cancer pathway from first symptom to treatment and to explore relationship between symptoms, delay and survival. Methods: Newly diagnosed lung cancer patients, referred to Oncology clinics in Norfolk 2008–2012, completed systematic questionnaires regarding date of onset of each symptom, MRC dyspnoea score and% weight loss. GPs also completed questionnaires. Additional patient, pathway and tumour data were retrieved from hospital records. The cancer pathway was recorded in five phases: 1) first symptom to GP presentation, 2) to secondary care (SC) referral, 3) to SC appointment, 4) to MDT meeting or date of diagnosis and 5) to treatment commencing. Results: Of 379 patients, mean age was 70.1 years, staging was: I-II (13.7%), III (34.3%) and IV (52%). Cohort survival was 6.1% with minimum follow-up of 39 months. Mean phase lengths were 221.8, 45.8, 10.7, 21.3, 34.7 days for phases 1–5 respectively. Phase 1 was significantly longer (p < 0.01). Mean phase 1 was shorter in stage III-IV than I-II, 200 and 245 days respectively (p < 0.05), in ex-/never-smokers (191.6 days) than smokers (264.2 days) (p = 0.022) and if first symptom was haemoptysis compared to cough or dyspnoea. 36.9% patients felt they delayed seeing their GP. Commonest reasons were: thinking symptoms were insignificant (35%), anxiety (28.6%) and denial (20%). Good correlation was seen between patient and GP reported dates. Reported symptoms included (% initial symptoms in parenthesis): cough 71% (62.8%), dyspnoea 62.8% (27.2%, chest pain 37.7% (8.7%), haemoptysis 28% (4.2%). Symptoms conferring increased hazard of death were defined as B symptoms. These were: grade 4/5 dyspnoea, hoarseness or loss of voice, metastatic pain and systemic symptoms (HRs 1.77, 1.53, 2.21, 1.93 respectively, p < 0.001). Patients with initial cough/mild dyspnoea have means of 127/210 days before B symptoms develop. Overall no relation was found between phase lengths 1–4 and survival. Survival increased if phase 5 was >31 compared to ≤31 days (HR 0.74, p = 0.006). Conclusions: Phase 1 is longest. There is no relation between phase length and survival except in phase 5. Symptoms are more important to survival than delay. Effective therapy started within 3 months (before B symptoms) could increase survival.